The development of leadership in model youth football coaches - Pankow, K.; Mosewich, A. D.; Holt, N. L. (The Sport Psychologist, 2018)
The purpose of this study was to examine perceptions of leadership styles in model youth football coaches. Six award-winning youth football coaches participated, and each was interviewed twice. Within a qualitative descriptive framework, deductive analysis was completed to identify the coaches` leadership styles, using the charismatic, ideological, and pragmatic model of outstanding leadership. Whereas pragmatic leadership behaviors were most frequently identified, all coaches appeared to have mixed leadership styles. Inductive analysis was then used to examine factors that influenced the coaches` leadership development. Identified themes were role models, networks of coaches, experience and reflection, and formal, nonformal, and informal learning. These were consistent across all the coaches, regardless of leadership style. This study therefore provides new insights into the perceived use of pragmatic behaviors in mixed leadership styles in model youth sport coaches and indicates that similar factors contributed to their leadership development.